Analisis Produktivitas Mesin Buffing Menggunakan Metode Overall Equipment Effectiveness (OEE) Di PT. XYZ Cikarang, Jawa Barat - Oktari Rabiatussyifa; Fahriza Nurul Azizah; Azizah Dian Ardhani (Peneliti.net, 2022)
This study discusses the analysis of the productivity of the buffing machine at PT. XYZ Cikarang, West Java. PT. XYZ is an industry that stands in the field of car body parts for four or more wheeled motor vehicles and industrial services for various special works of metal and metal goods. The method used in this research is Overall Equipment Effectiveness (OEE). The purpose of this study is to evaluate the condition of the buffing machine, which often occurs in damage which causes a decrease in machine productivity and production. As a result of these problems, it is necessary to repair machines which incur costs and the production process becomes constrained. Overall Equipment Effectiveness (OEE) is a method for measuring engine performance by taking into account the three important ratios, namely, Avaibility Rate, Performance Rate and Quality Rate. The results obtained from this study are the Avaibility Rate and Performance Rate values ​​are still below the standard they should be, namely the Avaibility Rate value of 61.36% and the Performance Rate value of 54.09%.